Effect of nitrogen content on high-temperature stability of hard and optically transparent amorphous Hf-Y-Si-B-C-N coatings. Issue 4 (15th February 2023) - Farhadizadeh, A.; Vlček, J.; Houška, J.; Haviar, S.; Čerstvý, R.; Červená, M.; Zeman, P.; Matas, M.
Abstract: We study the effect of nitrogen content on functional properties, thermal stability and oxidation resistance of hard and optically transparent amorphous Hf-Y-Si-B-C-N coatings prepared by pulsed magnetron sputtering. Ab-initio simulations are performed to link the experimentally obtained properties with the atomic and electronic structures of the fabricated materials. It is shown that the content of N in the material, varied from subsaturation 46 at.% to saturation 51 at.%, is of significant importance for the optimization of thermal stability and tuning the refractive index and extinction coefficient. We identify an optimum N2 content in the plasma and in turn N content in the coatings which outperform the previously introduced high-temperature material Hf6 Y2 Si29 B12 C2 N45 . The results constitute a progress in the efforts to combine multiple functional properties with exceptional (above 1300 °C) thermal stability and oxidation resistance.